2013
DOI: 10.1038/nrmicro3033
|View full text |Cite
|
Sign up to set email alerts
|

Transposon insertion sequencing: a new tool for systems-level analysis of microorganisms

Abstract: Our knowledge of gene function has increasingly lagged behind gene discovery, hindering our understanding of the genetic basis of microbial phenotypes. Recently, however, massively parallel sequencing has been combined with traditional transposon mutagenesis in techniques referred to as transposon sequencing (Tn-seq), high-throughput insertion tracking by deep sequencing (HITS), insertion sequencing (INSeq) and transposon-directed insertion site sequencing (TraDIS), making it possible to identify putative gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
407
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 448 publications
(409 citation statements)
references
References 68 publications
(76 reference statements)
2
407
0
Order By: Relevance
“…However, genome wide screening and identification of all genes involved in tolerance has been a limiting factor, which in the last years have been overcome through the use of next generation sequencing (NGS) techniques. Transposon insertion sequencing (Tn‐seq) (Figure 1a), enables high‐throughput identification of genomic regions involved in the survival of cells when exposed to various conditions (Barquist, Boinett, & Cain, 2013; van Opijnen & Camilli, 2013). A number of organisms have been investigated using this technique, thereby successfully identifying genes important for growth under different stress conditions, essentially by simultaneously investigating the fitness of all single mutants (Gawronski, Wong, Giannoukos, Ward, & Akerley, 2009; Langridge et al, 2009; Lennen & Herrgård, 2014; Santiago et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, genome wide screening and identification of all genes involved in tolerance has been a limiting factor, which in the last years have been overcome through the use of next generation sequencing (NGS) techniques. Transposon insertion sequencing (Tn‐seq) (Figure 1a), enables high‐throughput identification of genomic regions involved in the survival of cells when exposed to various conditions (Barquist, Boinett, & Cain, 2013; van Opijnen & Camilli, 2013). A number of organisms have been investigated using this technique, thereby successfully identifying genes important for growth under different stress conditions, essentially by simultaneously investigating the fitness of all single mutants (Gawronski, Wong, Giannoukos, Ward, & Akerley, 2009; Langridge et al, 2009; Lennen & Herrgård, 2014; Santiago et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Transposondirected insertion site sequencing (TraDIS, similar to Tn-seq), a PCR-based next generation sequencing technique that determines the location and abundance of transposon insertions in a population, showed that the library contained 60,000 independent insertion sites ( Fig. 2A), which represents approximately 20-fold coverage of the S. aureus genome (12,13). The high saturation of the transposon library enabled us to screen for genes that interact with WTAs by using tunicamycin to turn off WTA synthesis.…”
Section: Significancementioning
confidence: 99%
“…We reasoned that insight into distinct functions of TAs could be gleaned by identifying their genetic interactions. The recent merging of classical transposon mutagenesis with high-throughput next-generation sequencing (e.g., TraDIS, Tn-seq) has enabled parallel genotype-phenotype profiling and functional mapping for large collections of mutants (12,13). These methods have been used to identify genetic factors that influence susceptibility to lethal antibiotics (14), but can also be applied to map cell envelope networks.…”
mentioning
confidence: 99%
“…High-throughput genomic approaches such as transposon sequencing (Tn-seq) have been used to identify genetic elements required for in vitro and in vivo fitness (8). Tn-seq allows for simultaneous assessment of the abundance of tens or hundreds of thousands of individual transposon mutants after growth in a selective condition (e.g., in vivo infection model) (9)(10)(11).…”
mentioning
confidence: 99%